Higher Trait Impulsivity and Altered Frontostriatal Connectivity in Betel-Quid Dependent Individuals - Qian, Zhaoxin; Liu, Shaohui; Zhu, Xueling; Kong, Lingyu; Liu, Neng; Wang, Dongcui; Jiang, Canhua; Zhan, Zhongyuan; Yuan, Fulai (Frontiers in Human Neuroscience, 2020)
Objective: Betel quid dependency (BQD) is characterized by functional and structural brain alterations. Trait impulsivity may influence substance dependence by impacting its neurobiological underpinnings in frontostriatal circuit. However, little is known about the trait impulsivity and its neural correlates in individuals with BQD. Methods: Forty-eight participants with BQD and 22 normal controls (NCs) were recruited and scanned on a 3T MRI scanner. Barratt impulsiveness scale (BIS) was used to measure trait impulsivity: motor, attention, and no plan impulsivity. We used the voxel-based morphometry (VBM) to assess the relationship between trait impulsivity and gray matter volumes. The relevant clusters identified were served as regions of interest (ROI) seeds. The whole-volume psycho-physiological interactions (PPI) analysis was used to investigate the changes of functional connectivity related to ROI seeds in the cue reactivity task condition (BQ and control images). Results: Behaviorally, the BQD group showed significantly higher trait impulsivity including motor and no plan impulsivity than the NCs group. VBM analyses showed that motor impulsivity was negatively associated with gray matter volume of right caudate in the whole sample. No difference of gray matter volume between two groups was observed. PPI analyses showed that there was a significantly decreased functional connectivity between right caudate and right dorsolateral prefrontal cortex (DLPFC) when watching BQ related images than control images in individuals with BQD. Furthermore, functional connectivity between right caudate and right DLPFC was negatively correlated with BQ dependency scores. Conclusions: Our study demonstrated the structural basis of trait impulsivity in the caudate and provided evidence for abnormal interactions within frontostriatal circuits in individuals with BQD, which may provide insight into the selection of potential novel therapeutic targets for treatment of BQ dependency.